Auf den Spuren muslimischer Identitätspolitiken im NSU-Diskurs - Jacob Chilinski (Zeitschrift für Junge Religionswissenschaft)
This paper is an examination of articles from an Islamic online magazine about the NSU (National Socialist Underground), with regard to Stuart Hall's theory about the concept of identity. Based on his concept of identity as a never-ending process, identity can only be understood as a positioning in discourses and in distinction to the Other. Through a critical discourse analysis of the online magazine IslamiQ, it becomes evident how the experience of injustice of the NSU assassinations, the NSU investigations, political enlightenment, and the discourse of society as a whole can affect Muslim-Turkish identity politics. The thesis postulated here is that in the NSU discourse in IslamiQ, religion enables a place of identification and marks affiliations.